The principles of surgical treatment of breast cancer in accordance with oncological requirements and enabling easy breast reconstruction in case of mastectomy - Janusz Kruszewski, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2002)
The treatment of breast cancer has been performed for many centuries. Fundamental changes concerning methods of treatment of this disease were introduced in XVI century. In XVIII century scientific basis was created for breast amputation because of breast cancer. In XXI century modified radical mastectomy still remains one of the methods used in the treatment of breast cancer. Apart from oncological demands this method must fulfill the requirement of quick patient's return to full physical activity and maximally prevent from complications associated with amputation performed. Surgical treatment must also enable easy breast reconstruction. The important components of this approach remain: proper skin flap creation and preservation of many sensory and motor nerves with accompanying vessels. Flap creation concerns division between subcutaneous tissue and superficial layer of superficial fascia enveloping the whole breast parenchyma. Fascia should be left intact. Consecutively breast is removed from chest wall with deep fascia covering pectoralis major and serratus anterior muscles, and with deep layer of superficial fascia separating breast parenchyma from deep fascia. While removing tissues from axilla we should not exceed the entero-lateral edge of latissimus dorsi muscle, and axillary vein in order not to destroy lymphatic routes lying there. The preservation of motor innervation of muscles bordering the armpit is essential to surgical breast reconstruction. Among nerves, which particularly should be preserved are: thoracodorsal nerve, long thoracic nerve, intercostobrachial cutaneus nerve, and anterior thoracic nerves - medial and lateral. Preservation of intercostobrachial nerve is not obligatory. However, if the nerve remains intact, the sensory innervation of quite wide skin area on medial upper part of arm is saved. Good access to the apex of axilla may be achieved by opposite expansion of pectoralis major and pectoralis minor muscles with retractors. It enables the pectoralis minor muscle preservation and at the same time creates conditions for easier preservation of branches of medial pectoral nerve.